PENERAPAN METODE FUZZY SERVICE QUALITY (SERVQUAL) UNTUK MENGANALISA KEPUASAN PELAYANAN PENDIDIKAN PADA JURUSAN ILMU KOMPUTER FAKULTAS SAINS DAN TEKNIK UNIVERSITAS NUSA CENDANA - Roswita R Ligoresi; Sebastianus Adi Santoso Mola; Nelci D Rumlaklak (Universitas Nusa Cendana, 2017)
In carrying the service of education, Departmen Of Computer Science Faculty Of Science And Technique University Of Nusa Cendana, trying to give the service that can be contented the students. So far the departmen doesn’t know how the assessment of students against the service given. The survey of students statisfaction can be a manner to deliver what they feel and what is the hope of students against the service of education. Fuzzy service quality (servqual) method can be used to analyze the statisfaction of service. The concept of fuzzy is used to help the respondent for giving value that more objective, while the servqual method define the statisfaction of service as how far the difference between the facts and the hope on the service that is received by respondent. This method have five dimention that are tangibles, reliability, responsiveness, assurance dan emphaty. The result of service statisfaction analysis in Computer Science Department using the fuzzy method in the academic year 2016/2017 the value is GAP -14.3197, that means the giving service is not statisfy. Based on the result of analysis gived repair recommendation of each dimention that is the value of GAP is smallest negative.